(untitled) (Open International Journal of Informatics, 2023)
A company’s architecture significantly affects how much it is worth. Enterprise Architecture (EA) is the term used to describe the ideas and standards that guide the execution of information, technology, and business mission in defence companies. The main objective is to align information technology and business strategy better. For this project, we selected Defence Technologies Sdn Bhd (DefTech) for the case study in implementing the EA. the purpose of this research is to include the as-is and to-be scenarios in detail of each division in the organisation by using DoDAF. DefTech is in the security and defence industry. The main aim is to implement Cybersecurity for data security and asset planning since they supply and produce armoured and logistic vehicles specifically for military and homeland security. The As-Is and To-Be scenarios for DefTech were explained, and data leak protection has been added as the future architecture for the organisation. The component will increase cybersecurity protection and traceability during data leakage. Implementing and enforcing a DoDAF standard reduces inefficiencies in enterprise security and identifies weaknesses. EA has shown potential utility for designing integrated architectures for a business on its own. Still, it can also act as the hub for other initiatives to govern the collaborative enterprise, particularly those centred on security.